2016
DOI: 10.5530/jyp.2016.3.14
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Evaluation of Adverse Drug Reactions Due to Cancer Chemotherapy in a Tertiary Care Hospital in South India

Abstract: Introduction: To evaluate the adverse drug reactions (ADRs) due to cancer chemotherapy in a tertiary care hospital in South India. Materials and Methods: This was a retrospective descriptive study. The data was obtained from patients who developed, at least, one ADR due to cancer chemotherapy during the period June 2014 to May 2015. The causality of the ADRs were evaluated by WHO-UMC causality assessment system and Naranjo's ADR probability scale, the severity of ADRs were assessed by Hartwig and Siegel ADR se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 16 publications
3
6
2
2
Order By: Relevance
“…Our finding is similar to the study carried out by Sharma et al [5] that showed adverse effects in the 41-60 years age group. This finding is also similar to the report of Pai et al [6] who also reported average age of subjects 55.98 years and 52.96 years in men and women respectively and likewise, a study of Behera et al [7] which showed adverse reactions in 41-60 years age group was highest. This can be because of the high occurrence of cancers in this particular age group.…”
Section: Discussionsupporting
confidence: 91%
“…Our finding is similar to the study carried out by Sharma et al [5] that showed adverse effects in the 41-60 years age group. This finding is also similar to the report of Pai et al [6] who also reported average age of subjects 55.98 years and 52.96 years in men and women respectively and likewise, a study of Behera et al [7] which showed adverse reactions in 41-60 years age group was highest. This can be because of the high occurrence of cancers in this particular age group.…”
Section: Discussionsupporting
confidence: 91%
“…This was contrary to the findings of Bellare, et al ., (2016) who showed hyponatremia (12%) and infection (9%) as the most common ADR for males and hyponatremia (9.8%), neutropenia (11.8%) in females. 10 The occurrence of neutropenia was very less when compared to other studies. Gastrointestinal and haematological ADRs were frequently observed in the current study which resembles the study done by Thennarasu, et al, (2015).…”
Section: Doxorubicincontrasting
confidence: 99%
“…Similar results were reported by other studies [12 , 14] Most common cancer diagnosed was Bronchogenic carcinoma 21.53% , Carcinoma breast 18.46% , followed by carcinoma larynx 15.38% and carcinoma cervix 7.69%. This was similar to other studies [12 , 13] Malik et al and Poddar et al have reported lung and breast cancer as the most common [11,15] wheras Sunil Bellare et al reported oropharyngeal cancer as the commonest cancer reported [19] . Surindiran et al reported cervical cancer as the commonest cancer [16] The differences found in our study may be due to variation in geographic regions, food habits and life styles, occupational and environmental conditions Commonest ADR reported in our study were nausea & vomiting 17.11 % .followed by Headache 8.02% , Anxiety and Diziness 6.95 %.…”
Section: Discussionsupporting
confidence: 90%
“…There was no certain reaction as rechallenge was not done in any of the patient. Good correlation between the two scales of assessment was in agreement with Mittal et al and Sunil Bellary et al [19,20] However few other studies reported poor correlation between the scales [20 , 21] Causality assessment is to some extent subjective , so a definitive inferences may differ between two observer which was commented by other researchers as well [22,23] Hartwig and Siegel scale assessed most of the reactions as "moderate " 62.56% followed by "mild " 34.75% and "severe"2.67% and did not warrant withdrawl of the concerned drugs except in two patients who experienced features of anaphylaxis and were treated accordingly. This was in agreement to a study conducted by Sharma et al [6] None of the drugs caused lethal ADR .…”
Section: Discussionsupporting
confidence: 89%